Eager beavers v. lazy slugs: selection effects in experiments with social preferences - Eckel, Catherine; Wilson, Rick K.; Youn, Sora (Journal of the Economic Science Association, 2024)
We ask whether social preferences measured in subjects who come to the laboratory when invited are systematically different from those of subjects who only respond when an online option is available. Subjects participated in two types of third-party (other–other) dictator games and a trust game, either in the lab or on-line. In the third party dictator games, the dictator divides $20 between two other individuals, one of whom is a member of their in-group. (We also varied types of in-group between a real group and an artificial group.) In the trust game, the first-mover decides how much of the endowment to send to the second-mover. The second-mover receives the amount sent tripled by the experimenter and decides how much to send back to the trustee. Across all the games, we find no statistically significant differences in social preferences measured in-lab and on-line.